Decomposition And Settlement Behaviour Of Municipal Solid Waste - Awang, Norrimi Rosaida (2011)
Understanding the behavior of municipal solid waste settlement and decomposition is critical in managing a good landfill system. This study was conducted in order to develop understanding on MSW as it undergoes settlement and decomposition process through observation of individual waste behaviour in laboratory. The examination into the behaviour of individual waste was carried out due to the fact that real wastes are very heterogeneous and complex if it was to be analyzed at once. Eight types of waste namely Spinach, Rice, Fish, Meat, Spinach and Fish, Rice and Fish, Rice and Spinach, and Municipal mix were experimented.